Effect of intravenous versus inhaled anesthetics on blood-brain barrier dysfunction and neuroinflammation in elderly patients undergoing major surgery: study protocol of a randomized controlled trial - Wongook Wi; Hyo-Jin Kim; Sira Bang; Oh Joo Kweon; Doyeon Kim; Eun Jung Oh (Trials)
Abstract Background Postoperative cognitive dysfunction (POCD) is one of the major complications after surgery, with devastating clinical outcomes. Although POCD is a condition with a multifactorial pathophysiology, blood-brain barrier (BBB) dysfunction and neuronal injury have been shown to play a critical role, especially in the elderly. Previous studies have demonstrated that the choice of anesthetics affect BBB permeability and neuroinflammation. However, most studies are carried out on animals, with limited research undertaken on humans. Therefore, we will compare the effect of intravenous anesthetics and inhaled anesthetics on BBB dysfunction and the change of inflammatory markers after surgery. Methods One hundred and fifty-four patients who are 60 years of age or older undergoing major surgery for more than 2 h will be randomly allocated to two anesthetics groups (intravenous, inhaled) in a 1:1 ratio. In the intravenous anesthetics group (group P), propofol will be infused with a target-controlled infusion (TCI) system throughout the entire surgery. In the inhaled anesthetics group (group G), bolus injection of propofol will be administered for loss of consciousness, and simultaneously sevoflurane will be initiated for the maintenance of anesthesia. The primary outcome is the change in serum S100 calcium binding protein β (S100β) at four time points: before induction of anesthesia, at the end of surgery, 4 h after surgery, postoperative day 1. Secondary outcomes include changes in the inflammatory markers, serum interleukin (IL)-6, IL-8, tumor necrosis factor (TNF)-α, and C-reactive protein; the incidence of delirium; and the change in the cognitive function between groups. In patients pre-scheduled for postoperative intensive care unit admission, the cerebrospinal fluid/serum albumin quotient (Qalb) between the two groups will be compared before and after surgery, and change in inflammatory markers in serum and CSF will be analyzed in relation to the Qalb. Discussion The current study will compare the effect of intravenous versus inhaled anesthetics on blood-brain barrier permeability and, as a result, the difference in neuroinflammation in elderly patients. Also, the study results will provide additional information to develop intraoperative anesthetic strategies to reduce POCD. Trial registration The trial was prospectively registered at Clinical Trials protocol registration with identifier 2310-117-126 on April 9, 2024.